Arnold’s cat map secure multiple-layer reversible watermarking - Aulia Arham; Novia Lestari (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Reversible watermarking is a novel approach to digital copyright protection that allows the embedding of watermarks into digital data using multiple layers while retaining the ability to recover the original content without data loss. This method provides a unique solution for securing digital data while maintaining the integrity and quality of the content. Nonetheless, new challenges have emerged with the increase in attacks on this method, as reversible watermarking methods lack security keys, making it easy to extract and modify hidden data. In this paper, we present a method for multiple-layer reversible watermarking with security keys, with the goal of addressing the challenges posed by attacks and improving data protection within embedded content. The method uses arnold’s cat map to scramble images, and data embedding in predetermined iterations serves as the methods security key. We put the method through its paces with six grayscale images. With this method, the embedding capacity can reach 2.999 bpp across four layers of embedding, while the visual image quality can reach 22.01 dB. The outcomes from this approach are that the security of multiple-layer reversible watermarking can be enhanced while preserving the capacity to embed data in each layer.